PENERAPAN TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS V SEKOLAH DASAR - Muamanah, Husnul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aimed to obtain information that is clearly about the application of jigsaw type to increase student activity on civic education learning in Class V Sekolah Dasar Negeri 34 Pontianak Kota West Borneo province. The research method that used is descriptive method. Form of research is the Classroom Action Research (Classroom Action Research) collaborative. Setting research in class V the number of students as many as 35 people. This research was conducted as many as three cycles with the results obtained namely, the ability of teachers plan learning in the third cycle obtained average value of 3,94 with the excellent category. While the ability of teachers to implement teaching in the third cycle obtained an average value of 3.95 with the excellent category. For the percentage of students in the third cycle of activity. For the percentage of student activity in the third cycle of 84.27% with the very high category. Thus research of application of jigsaw type on civic education learning can enchance the activity the of five grade students.Â Keywords: Student Activities, Jigsaw Type.